خير الدين باشا التونسي وإصلاحاته1820م -1890م - خديجة محمدي; د/ بوقرين عيسى (جامعة عمار ثليجي الاغواط, 2023)
الملخص: تناولت دراستنا لشخصية خير الدين التونسي، والذي يعتبر من الشخصيات البارزة في القرن ،19م سواء للدولة العثمانية بصفة عامة أو تونس بصفة خاصة، الذي يمثل احد رواد النهضة الفكرية في العالم العربي الإسلامي، ورمز من رموز الحركة الإصلاحية في تونس، ونظرا للمكانة التي اكتسبها خير الدين لدى المثقفين من المشارقة، الذين تأثروا بكتابه وقرروا ترجمته و ذكره في مؤلفاتهم، كأحمد أمين والزركلي، وهذا ما جعله يتربع على مسرح الأحداث في الفترة الحديثة، محاولا إصلاح الأوضاع التي كانت تعيشها تونس آنذاك، إلى انه لم يتمكن من تطبيق ما رسمه من أهداف نتيجة من ظروف وأزمات داخلية وخارجية عرقلت مسار الصالح. Abstract: Our study dealt with the personality of Khair al-Din al-Tunisi, who is considered one of the prominent personalities In the 19th century AD, whether for the Ottoman Empire in general or Tunisia in particular, which represents One of the pioneers of the intellectual renaissance in the Arab Islamic world, and a symbol of the reform movement In Tunisia, where he sought to implement his reform ideas, which were inspired by his book “I Rise Tract", which we can put among the books that contributed significantly to the awakening of The feeling of renewal within Arab societies, and given the position Khair El-Din has gained among Intellectuals from Al-Masharqa, who were influenced by his book and decided to translate it and mention it in their books, such as Ahmed Amin And Al-Zarkali, and this is what made him sit on the scene of events in the modern period, trying to fix the situation which Tunisia was experiencing at the time, until he was unable to implement the goals he had drawn as a result From internal and external circumstances and crises that hindered the path of righteousness.